THE ROAD TO PERFECTION - Kambarov Nodirjon Sattarovich (Scholar Express Journal, 2022)
This article discusses martial arts, their development, popularity, biological approach, inner strength and significance for human health. Eastern martial arts plays an important role in the education of a person in the physical, spiritual, spiritual and aesthetic.
Keywords: Martial arts; a perfect person; an aspect of healing; mental